2017
DOI: 10.1111/jcmm.12946
|View full text |Cite
|
Sign up to set email alerts
|

3D culture increases pluripotent gene expression in mesenchymal stem cells through relaxation of cytoskeleton tension

Abstract: Three‐dimensional (3D) culture has been shown to improve pluripotent gene expression in mesenchymal stem cells (MSCs), but the underlining mechanisms were poorly understood. Here, we found that the relaxation of cytoskeleton tension of MSCs in 3D culture was critically associated with the expressional up‐regulation of Nanog. Cultured in spheroids, MSCs showed decreased integrin‐based cell–matrix adhesion but increased cadherin‐based cell–cell interaction. Different from that in 2D culture, where MSCs exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
72
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 64 publications
14
72
2
Order By: Relevance
“…To investigate whether decreasing actin polymerization causes the reduction of MSC size, we examined the influence of 3D cell culture, CytoD treatment, and CD29 blockade on actin polymerization and cell size. Consistent with our previous findings , 3D culture dramatically reduced the amount of F‐actin filament bundles in the cytoplasm in immunofluorescence analysis (Fig. A) and the levels of total actin and F‐actin as determined by Western blot (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…To investigate whether decreasing actin polymerization causes the reduction of MSC size, we examined the influence of 3D cell culture, CytoD treatment, and CD29 blockade on actin polymerization and cell size. Consistent with our previous findings , 3D culture dramatically reduced the amount of F‐actin filament bundles in the cytoplasm in immunofluorescence analysis (Fig. A) and the levels of total actin and F‐actin as determined by Western blot (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Besides the reduction in cell size, we found that 3D spheroid culture dramatically decreased the expression of β1 integrin (CD29) along with several α intergrin binding chains in MSCs . In addition, the cells exhibited a marked reduction in the amount of actin filament bundles . Previous studies suggest that actin cytoskeleton play a role in regulating cell size; actin polymerization inhibits microparticle shedding and disruption of the cortical actin network increases the number of microparticles generated by leukocytes .…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The increased COX-2 expression is in turn due to the unbundled form of F-actin (i.e. a more relaxed form of actin, in comparison to the dense stress fibers observed in 2D) near the edge of the MBs, which was reported to sustain NF-κB activity 50 and to downregulate COX-2 transcriptional repressors 51,52 . Therefore NF-κB has a high activity in the outer layers of the MB, where it locally promotes COX-2 expression.…”
Section: Discussionmentioning
confidence: 98%
“…For example, human placenta MSC spheroids displayed lower expression of integrin β1 compared to normal 2D culture, leading to a decrease of cell-ECM interaction and enhancement of MSC stemness. By other approaches to release cytoskeleton tension, the stemness of MSCs was promoted as well, revealing the negative relationship between stemness and cytoskeleton tension in MSCs [71]. In addition to cell-matrix interaction, the cadherin-mediated cell-cell interaction cannot be ignored.…”
Section: Physical and Chemical Factors Affecting Cell Behaviors In Scmentioning
confidence: 99%